CENTRAL BANK DIGITAL CURRENCY (CBDC): A SENTIMENT ANALYSIS AND LEGAL PERSPECTIVE - Aisyah As-Salafiyah; Aam Slamet Rusydiana; Ihsanul Ikhwan (Journal of Central Banking Law and Institutions, 2023)
Bank Indonesia plans to issue a digital rupiah in the Central Bank Digital Currency (CBDC) development project, the official digital currency issued by the central bank. This study aims to review the perceptions of the scientific literature regarding the CBDC theme from a legal perspective. Its nature is still new and has not been widely implemented by various countries worldwide, making this theme interesting for further study. This study uses a qualitative method with a sentiment analysis approach. The research object is 50 papers published by Scopus-indexed journals until December 12, 2022. The data is then processed using the SentiStrength software, which can be used in conducting sentiment analysis. CBDC is an innovation that is currently being developed by various countries in the world. The results of this study indicate differences in sentiment trends from various pieces of literature, where of the five classifications of sentiment, sentiment showing high positive and high negative amounts to 0%. The positive sentiment is 30%, the negative sentiment is 26%, and the neutral sentiment is 44%. This finding indicates that the dominant sentiment is neutral, where positive and negative levels are equal, followed by positive sentiment and then negative sentiment. The results of this sentiment analysis are an overview that can serve as basic research for regulators, practitioners and academics as valuable insights that can help provide an understanding of the scientific literature's perception of CBDC so that it can be considered in decision making. This research is the first study to conduct sentiment analysis on the scientific literature on the CBDC theme.